The Influence of Employee Competence and Discipline on the Quality of Public Services at the Vocational and Productivity Training Center (BBPVP) Kemnaker Makassar - Ira Sri Wahyuni; Mujahid; Rosnaini Daga (International Journal of Global Sustainable Research, 2026)
Ira Sri Wahyuni. 2026. The Influence of Employee Competence and Work Discipline on Public Service Quality at the Makassar Center for Vocational and Productivity Training (BBPVP), Ministry of Manpower. (Supervised by Supervised by Mujahid and Rosnaini Daga). This study employs a quantitative approach using a survey method. The population consists of all employees at BBPVP Makassar, with a sample of 77 respondents determined through a saturated sampling technique. Data collection was conducted by distributing questionnaires using a Likert scale. This study aims to analyze the effect of employee competence on public service quality, the effect of work discipline on public service quality, and the simultaneous effect of employee competence and work discipline on public service quality at the Makassar Center for Vocational and Productivity Training (BBPVP), Ministry of Manpower. The research results indicate that employee competence has a positive and significant effect on the quality of public service. Work discipline also has a positive and significant effect on the quality of public service. Simultaneously, employee competence and work discipline have a positive and significant effect on the quality of public service. The coefficient of determination results shows that the variation in public service quality can be explained by employee competence and work discipline, while the is influenced by factors outside the research model. The most dominant variable influencing the quality of public service is employee competence